AKIBAT HUKUM KERUGIAN KEUANGAN NEGARA DALAM PROSES PENYIDIKAN TINDAK PIDANA KORUPSI - Denny Latumaerissa (Faculty of Law, Universitas Pattimura, 2015)
Corruption is a serious problem, this criminal act could endanger the stability and safety of society, endanger social, economic and political development, and also could endanger the value of democracy and morality because slowly this action becoming a major threat for the aim of just and prosperous society. The state indemnification could be done through two ways which are using the criminal instrument and private instrument. The investigation phase becoming one of the most important phases in the state indemnification process through the criminal instrument. In this stage, the state indemnification could be done by the suspect. Although the problem could arise from the misinterpretation from the investigator that consider the state indemnification by the suspect in the investigation phase could decrease and even stopped the investigation by the investigators. Juridically, the state indemnification that occurred in the investigation phase, prosecution, or examination in the court only could influence in the determination of light-weight of criminal for the suspect or defendant, but not eliminating the nature of against the law itself.